Optimizing the Tracking of Falls in Studies of Older Participants: Comparison of Quarterly Telephone Recall With Monthly Falls Calendars in the MOBILIZE Boston Study - Hannan, Marian T. (Oxford University Press, 2010)
Tracking falls among elders is challenging. In this reliability study, which took place between October 2007 and February 2008, the authors compared participants’ daily recordings of falls on calendars with a telephone survey of recall of falls over the previous 3 months within the population-based MOBILIZE Boston Study cohort, a cohort of 765 elders. From the cohort, 218 participants were randomly selected. Falls were tracked prospectively on daily calendars (mailed back monthly). Telephone recalls of falls over the previous 3 months were conducted in January and February 2008. Agreement, sensitivity, and specificity were calculated to compare the occurrence of falls as determined by 3-month recall with falls recorded by daily calendar (gold standard) during the same 3-month period. Results showed good agreement between recall and calendars: 27 persons reported a fall by both methods. However, while the 3-month recall correctly classified persons who did not fall (164 persons by both methods), it missed 25% of participants who fell (of 36 participants with a calendar-reported fall, 9 did not report a fall by telephone recall). Kappa was 0.74 (95% confidence interval: 0.68, 0.80), sensitivity was 75%, and specificity was 96%. Retrospective 3-month recall of falls resulted in underreporting of falls by as much as 25% compared with daily calendars. Calendars should be considered the preferred method of ascertaining falls in longitudinal studies.